DETERMINATION OF OBSTACLES TO NURSING STUDENTS QUESTIONING SEXUAL/REPRODUCTIVE HEALTH OF PATIENTS - KARASU, Fatma; POLAT, Filiz; BİRİMOĞLU OKUYAN, Canan (Göbeklitepe Medical Science Journal, 2021)
Aim: This study was performed with the aim of determining the obstacles of nursing students about questioning sick individuals about sexual/reproductive health. Material and Methods: The population for the cross-sectional research comprised a total of 637 students attending the nursing departments in two universities. Research data were collected with a web-based survey form in the digital environment prepared in line with literature information. Analysis of data used descriptive statistics of frequency, percentage, mean and standard deviation, in addition to the chi-square test for comparison of independent groups. Results: Of students, 71.7% had not received sexual/reproductive health lessons, 87% stated they required education as they did not have sufficient sexual/reproductive health counseling information and 47.1% stated they could not easily ask questions due to embarrassment. According to gender, feeling the need for education to be able to talk about sexuality, not having sufficient information and counselling about sexual/reproductive health, adequacy of information about nursing interventions for sexual/reproductive health and experiencing problems in assessing sexual/reproductive health-related problems of individuals attending health facilities were determined to have statistically significant differences (p<0.05). Conclusion: Most nursing students were identified not to have received sexual health lessons, did not have adequate information about sexual counselling and could not easily ask questions to individuals attending health facilities. It is recommended to deal with obstacles to questioning the sexual/reproductive health of patients and to ensure students have information, skills, and apparatus with sexual health lessons.